The concept of “genericity” in political economy - García-Cobián Jáuregui, Ramón (1993)
The author explains the concept of 'genericity' and maintains that it is essential for scientific models. Then, he defines the associated concept of 'exceptionality' and shows how some assumptions in political economics (like Marx's theory of the uniformity of the composition of capital or Morishima's industrial independence) are exceptional. Finally, he shows that successful Sraffian systems are generic.